Inhibition of Cyclin-Dependent Kinase Phosphorylation of FOXO1 and Prostate Cancer Cell Growth by a Peptide Derived from FOXO1 - Huarui Lu; Ping Liu; Yunqian Pan; Haojie Huang (Neoplasia: An International Journal for Oncology Research, 2011)
Increasing evidence suggests that FOXO1 possesses a tumor suppressor function. Inactivation of FOXO1 has been documented in many types of human cancer, and restoring the activity of FOXO1 holds promise for cancer treatment. In this study, we identified a FOXO1-derived peptide termed FO1-6nls that inhibits cyclin-dependent kinases 1 and 2 (CDK1/2)-mediated phosphorylation of FOXO1 at the serine 249 residue in vitro and in vivo. Overexpression of FO1-6nls in prostate cancer (PCa) cells not only blocked CDK1-induced cytoplasmic localization of FOXO1 but also augmented FOXO1's transcriptional activity. This effect of FO1-6nls requires its binding to CDK1 and CDK2. Moreover, the ectopic expression of FO1-6nls inhibited the growth of PTEN-positive DU145 PCa cells. Importantly, the growth-inhibitory function of FO1-6nls is dependent on FOXO1. Finally, the ectopic expression of FO1-6nls overcame CDK1-mediated inhibition of FOXO1-induced apoptosis of PCa cells. These results indicate that the FOXO1-derived peptide FO1-6nls can restore FOXO1's tumor suppressor function by specifically opposing CDK1/2-mediated phosphorylation and inhibition of FOXO1 and hence may have a therapeutic potential for the treatment of PCa.